"Can we all get along:"1 American political divisiveness in the 21st Century. Issue 4 (14th October 2020) - Duty, Ronald W.
Abstract: The current American political divisiveness follows prior divisive periods and is not unique. The simultaneous developments of a culture war and a partisan realignment helped to create division. Disagreement over the proper role of government completed the division. Race is a significant dividing social and political issue in America. For Reinhold Niebuhr, "Democracy is a method of finding proximate solutions to insoluble problems." Finding agreement over policing policy may be possible, but principled political compromise over underlying issues contributing to racial inequities is likely to be harder.